Analysis of the Impact of Economic Shocks on Indonesian Stock Market Returns - MOH. SAIFULLAH ADAM; Mohammad Nofal; Munawarah; Erwan Sastrawan Farid (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the return movements of the IHSG and eleven IDX sectoral indices during sequential external and domestic shocks from January 2025 to April 2026 using the 5-day EMA, skewness, kurtosis, and Sharpe Ratio. Based on 293 trading days, the results show nonlinear and highly responsive Composite EMA movements, with all sectors recording negative skewness and leptokurtic distributions. Industrials achieved the highest Sharpe Ratio (0.135), followed by Transportation (0.097) and Basic Materials (0.094), while Finance, Composite, and Non-Cyclical recorded negative values. These findings support higher-moment risk management in Indonesian sectoral portfolio analysis. Keywords: Economic Shocks; Stock Returns; Moving Average; Skewness; Kurtosis; Sharpe Ratio